COMPARATIVE PHYSICO-CHEMICAL AND PHYTO-CHEMICAL ANALYSIS OF TALISADI CHURNA WSR TO DIFFERENT MARKET SAMPLES - *Prabhavati C Kichadi; R S Hiremath; Kirankumar Hullatti (International Journal of Ayurveda and Pharma Research, 2019)
Talisadi Churna is a compound herbal formulation extensively used in disorders of upper respiratory tract and Gastro-intestinal tract. Formulation has greater demand due to its simple combination, therapeutic efficacy and methods of preparation and packaging due to which multiple companies prepare the formulation with due precision and safety evaluation. A current study was taken to evaluate in-house prepared sample of Talisadi Churna as per the AFI protocol and was compared to 3 different market samples. All the samples of Talisadi Churna were subjected to physico-chemical, preliminary phyto-chemical analysis and TLC. The study reveals that there is a significant difference is seen in the physico-chemical analysis and TLC, but there is no significant difference is seen in the preliminary phyto-chemical analysis.